Synthesis and biological properties of 9-r-3-(methylthio)- pyrazole[1,5-d] [1,2,4]triazolo[3,4-f][1,2,4]triazines - Fedotov, S. O.; Федотов, Сергій Олегович (Запорізький державний медичний університет, 2022)
The aim of the study. Synthesis of 9-R-3-(methylthio)pyrazole[1,5-d][1,2,4]triazolo[3,4- f][1,2,4]triazines and screening of their biological activity.
Keywords: тези доповідей